REGISTRATION APPLICATION AND EXAM SIGN IN BAHASA PARTICAL INSTITUTION COURSE (PEC) USING MICROSOFT VISUAL BASIC 6.0. - Binsar Manula; Susi Wagiyati P, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Information within or outside the computer recorded in memory. With other words, memory is a tool on a computer system that served to store information. Memory-duty work to accommodate the job at the time before and during after the work is carried out by the processor. While supporting memory or virtual memory is created to support or assist the working memory. Loading rates in the framework of a working memory which will cause all the order filled. After that, if there is a new tribe who need a place in the working memory, working memory is no longer able to accommodate the placement of another tribe. In order for the new rates can be accommodated within the working memory, there is interest in the context of memory-work that needs to be returned to the memory of supporters. Rates of return from the context in working memory to memory capacity requires a certain strategy. For that we need a way of placement and the return of the tribe. Known by fifo method and algorithm with the optimal method. Where to from these two methods will be compared, so we get the best possible way in the placement and return of the tribe.